EVALUATION OF SOMBO FLATS ASSOCIATED WITH ENVIRONMENTAL DEVELOPMENT - Adinda S.P.R Utami; Tara D. Saraswati; Lisa Amalia (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2015)
Homes as basic human needs have an important role in the growth of the inhabitants. In fact, many people do not have access to adequate housing. Surabaya as one of the big cities in Indonesia also has problems in providing decent dwelling for the residents of the city. Flats are built as one of the solutions for settlement problems in Surabaya. One of the settlement problems that are answered with the provision of flats is the Sombo flats. The Sombo flats were built in stages and has been operating since 1992. When viewed today, the existing condition of Sombo flat has undergone many functional shifts and quality degradation. In addition to the growing population, there are internal problems of the inhabitants such as low ecological cultural awareness. This research is a form of evaluation of the function and quality of Sombo flat with descriptive-qualitative method. From the evaluation and analysis conducted, it currently needs rejuvenation with ecological and sustainable community and environmental participation approach.